THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 KUBU IN CHANGING ACTIVE INTO PASSIVE SENTENCES - ', Hendro; Azhar, Fadly; K, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study is to find out the ability of the second year students of SMPN 1 Kubu in changing active into passive sentences. This research focuses on students’ ability in changing active into passive sentences, especially simple present tense, in terms of statements and questions. The data were collected using passive test with essay type. The test contained 28 items. The try out was conducted to check the validity and reliability of the test. Based on the research, it was found out that first: the mean score ability of the second year students of SMPN 1 Kubu in changing active into passive sentences is 49.57 (in the mediocre level). Second, the students’ mean score in changing active into passive sentence in term of statement is 63 ( in good level ) , and the lowest score that the students got in term of question is 53.14 and categorized into poor level. This means the students’ ability in changing active into passive sentences is mediocre level.Keywords , Ability, Active sentence, Passive sentence .